2021
DOI: 10.1186/s10194-021-01318-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced functional connectivity between habenula and salience network in medication-overuse headache complicating chronic migraine positions it within the addiction disorders: an ICA-based resting-state fMRI study

Abstract: Background Medication-overuse headache (MOH) is a relatively frequently occurring secondary headache caused by overuse of analgesics and/or acute migraine medications. It is believed that MOH is associated with dependence behaviors and substance addiction, in which the salience network (SN) and the habenula may play an important role. This study aims to investigate the resting-state (RS) functional connectivity between the habenula and the SN in patients with MOH complicating chronic migraine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The brain regions with increased FCD did not show changes in FC, which suggests that the increased FCD may be a transitory result of MOH (32). Our results (published in 2021) showed that patients with MOH and a history of chronic migraine, compared with the HCs and EM group, exhibited stronger FC of the bilateral habenular nuclei with the dorsal anterior cingulate cortices (dACC, a region in the salience network) and the bilateral insula/frontal operculum (33). As a core component of the brain anti-reward system, the lateral habenula receives input from limbic-forebrain and basal ganglia regions and sends output to the midbrain nucleus including the VTA and substantia nigra compacta (SNc) (34).…”
Section: Fmrimentioning
confidence: 43%
“…The brain regions with increased FCD did not show changes in FC, which suggests that the increased FCD may be a transitory result of MOH (32). Our results (published in 2021) showed that patients with MOH and a history of chronic migraine, compared with the HCs and EM group, exhibited stronger FC of the bilateral habenular nuclei with the dorsal anterior cingulate cortices (dACC, a region in the salience network) and the bilateral insula/frontal operculum (33). As a core component of the brain anti-reward system, the lateral habenula receives input from limbic-forebrain and basal ganglia regions and sends output to the midbrain nucleus including the VTA and substantia nigra compacta (SNc) (34).…”
Section: Fmrimentioning
confidence: 43%
“…Another study however demonstrated shared abnormalities of SN FC distinguishing both groups from HC, as well as FC alterations differentiating chronic migraine and chronic migraine with medication overuse (127). Furthermore, subjects with chronic migraine with medication overuse demonstrated heightened FC of the SN to bilateral habenulae compared with episodic migraine and HC (with no difference between episodic migraine and HC), which correlated with medication overuse duration (117). In an investigation of PACAP38-triggered migraine attacks, the authors demonstrated increased connectivity of SN seeds to right and left inferior frontal gyri during provoked attacks compared to baseline (56).…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Dai and colleagues [25], an increased functional connectivity between habenula and salience network was exhibited in CM relative to EM group. Habenula brings input from the hippocampus and basal ganglia structures, among others [49], while salience network (primarily composed of the anterior insula and dorsal ACC) collaborates in the integration of emotional and cognitive information [50].…”
Section: Evidence From Fmri Studiesmentioning
confidence: 92%
“…Of them, 22 were original articles, while 2 were review articles [14,15]. Results of the original articles were based on EEG (3 studies) [16][17][18], MEG (6 studies) [19][20][21][22][23][24], fMRI (10 studies) [25][26][27][28][29][30][31][32][33][34], and PET (3 studies) [35][36][37] (see Fig. 1c).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%